Hybrid MoM–PO analysis of multilayered SIW slot antenna with a dielectric slab radome. Issue 2 (25th March 2015) - Bayderkhani, Reza; Forooraghi, Keyvan; Arnieri, Emilio; Abbasi-Arand, Bijan
Abstract : A fast and efficient full-wave hybrid method for the analysis of a multilayered substrate integrated waveguide (SIW) based slot antenna/array radiating into a dielectric slab radome is presented. The antenna structure is modeled as a stacked parallel-plate waveguide hosting metallic posts and coupling and/or radiating slots. To account the radome effects on the SIW antenna, the physical optics method in conjunction with three-dimensional ray trace technique are used to analyze a dielectric slab radome staked on the aperture of the antenna. The field in the SIW structure is expressed by using an expansion in terms of vectorial cylindrical eigenfunctions. Enforcing the boundary conditions on posts yield the scattering amplitude, while slots are modeled as unknown magnetic currents which are found by solving the integral equation derived from the continuity of the field on the slot surface. A double-layered SIW cavity backed slot antenna radiating into a dielectric slab radome is analyzed, and the results compared with high frequency simulation software (HFSS) simulations. It will be shown that the proposed method is fast and efficient and gives results in very good agreement with the most common simulation tools.